EVALUATION OF THE PRODUCTION TECHNOLOGY OF MEAT PASTE - Федорив, Виктор; Прилипко, Татьяна (Modern engineering and innovative technologies, 2022)
The results of technological features, flow lines and modes of sterilization of meat pastes are given. Thanks to the development of a new method of aseptic canning, it became possible to intensify the heat treatment of the product and, as a result, to red